Balance in elite judo and its relationship with injuries - Lopez Diaz de Durana, A.; Stirling, J. R.; Zakynthinaki, M. S.; Rodriguez-Romo, G. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Balance and posture in general is often affected by the history of injuries: different injuries affecting the balance or movement pattern of the individual in different ways. The converse of this is also true, in as much as irregularities in an individual`s posture and balance can increase the likelihood of particular injuries. The aim of this study was to apply the model Stirling and Zakynthinaki (2004) and the tools presented in Zakynthinaki et al (2008) to examine the connection between injuries and the asymmetries in the balance of elite judokas. Methods 5 elite judokas took part in the study. Each judoka stood on a force platform and was perturbed from quiet upright stance, for the two legged and single legged position (Zakynthinaki et al, 2008; Stirling et al, 2007). The maximum correctable angles between the resultant ground reaction forces and the vertical in both the anteroposterior and mediolateral directions were obtained. A closed critical curve (Stirling and Zakynthinaki, 2004) was fit through the maximum correctable angles at which the judoka could lean. This critical curve was analyzed for asymmetries and the judokas completed a questionnaire regarding their history of injuries. Video was also taken of all the experiments in both the anteroposterior and mediolateral directions so as to allow us to observe some of the basic irregularities in the posture and movement patterns. Results A connection between the asymmetries in the critical curve and both the history of injuries and the current injuries was observed. In particular very strong asymmetries in the critical curve were shown to exist for those judokas who were injured when they completed the test. Discussion Injuries can result in muscle imbalances, postural problems, structural problems and hence as a result can cause asymmetric movement patterns which lead to differences in the ranges of motion on either side of the body. Such differences have been identified via the critical curve (Zakynthinaki et al, 2008; Stirling and Zakynthinaki, 2004). Our research has shown how these methods can be used to identify both current injuries and those which have occurred in the past (Stirling and Zakynthinaki, 2005).